50.4k views
4 votes
Write in slope intercept form, then convert to standard form Slope=1, y-intercept=-3​

User Benishky
by
5.6k points

2 Answers

2 votes

Slope = 1

y-intercept = -3, which can be expressed as (0,-3).

y - y_1 = m(x - x_1)

y -(-3) = 1(x - 0)

y + 3 = x

The slope-intercept form is

y = x - 3.

The standard form is Ax + By = C.

y = x - 3

3 = x - y

Done.

User Kintsukuroi
by
4.9k points
2 votes

Answer:

x + 3

Explanation:

Slope = 1

y intercept = 3

=> y = mx + c

=> y = 1x + 3

=> y = x + 3

User MathewS
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.